Fernando Pessoa's Book of Disquiet as a Dynamic Digital Archive - Portela, Manuel (2016)
The LdoD Archive is a dynamic digital archive based on Fernando Pessoa’s Livro do Desassossego [“L. do D.”] http://ldod.uc.pt. The Archive contains facsimiles and textual transcriptions of autograph witnesses (manuscripts, typescripts, printed texts) as well as textual transcriptions of four editions of the Book of Disquiet published between 1982 and 2012. All variations across the textual corpus have been marked up in TEI-conformant XML. This granular encoding has enabled us to automate comparisons between any 2, 3, 4 or 5 versions of any given fragment, both at the micro-scale of textual form, and at the macro-scale of bibliographic structure. Besides the set of functionalities related to the scholarly level of the archive, the LdoD Archive provides a set of software tools that allow readers to generate further content by creating their own editions and annotations within the archive’s virtual layer, and by writing their own variations based on specific passages. The research for this project culminated in a dynamic model for a digital archive, which brings collaborative computing techniques into the universe of critical editing and reading in digital media. This article discusses the conceptual and technical virtualization of the Book of Disquiet as a digital simulation of the dynamic nature of textual fields, and presents the project’s workflow from expert encoding to end-user interaction.